Gibberellins Producing Endophytic Fungus Porostereum spadiceum AGH786 Rescues Growth of Salt Affected Soybean - Hamayun, Muhammad; Hussain, Anwar; Khan, Sumera A.; Kim, Ho-Youn; Khan, Abdul L.; Waqas, Muhammad; Irshad, Muhammad; Iqbal, Amjad; Rehman, Gauhar; Jan, Samin; Lee, In-Jung (Frontiers in Microbiology, 2017)
In the pursuit of sustainable agriculture through environment and human health friendly practices, we evaluated the potential of a novel gibberellins (GAs) producing basidiomycetous endophytic fungus Porostereum spadiceum AGH786, for alleviating salt stress and promoting health benefits of soybean. Soybean seedlings exposed to different levels of NaCl stress (70 mM and 140 mM) under greenhouse conditions, were inoculated with the AGH786 strain. Levels of phytohormones including GAs, JA and ABA, and isoflavones were compared in control and the inoculated seedlings to understand the mechanism through which the stress is alleviated. Gibberellins (GAs) producing endophytic fungi have been vital for promoting plant growth under normal and stress conditions. We report P. spadiceum AGH786 as the ever first GAs producing basidiomycetous fungus capable of producing six types of GAs. In comparison to the so for most efficient GAs producing Gibberella fujikuroi, AGH786 produced significantly higher amount of the bioactive GA3. Salt-stressed phenotype of soybean seedlings was characterized by low content of GAs and high amount of ABA and JA with reduced shoot length, biomass, leaf area, chlorophyll contents and rate of photosynthesis. Mitigation of salt stress by AGH786 was always accompanied by high GAs, and low ABA and JA, suggesting that this endophytic fungus reduces the effect of salinity by modulating endogenous phytohormones of the seedlings. Additionally, this strain also enhanced the endogenous level of two isoflavones including daidzen and genistein in soybean seedlings under normal as well as salt stress conditions as compared to their respective controls. P. spadiceum AGH786 boosted the NaCl stress tolerance and growth in soybean, by modulating seedlings endogenous phytohormones and isoflavones suggesting a valuable contribution of this potent fungal biofertilizer in sustainable agriculture in salt affected soils.